Properties and active substances of hummus bean paste based on chickpea puree - M. W.M. Shehadeh (Новые технологии)
Introduction. Recently, there has been a growing interest in legumes, including chickpeas, as a source of protein and other nutrients. Hummus, a traditional Middle Eastern dish made from chickpea puree, is an excellent example of the use of legumes in cooking. In recent years, hummus has become a popular product in the diet, due to its nutritional value and ability to integrate into a variety of culinary traditions. There is also a growing interest among consumers in healthy eating, in which hummus plays a key role as a source of plant protein and other beneficial components.   The goal of the research was to determine the protein, vitamin and mineral content of hummus, as well as to evaluate its antioxidant activity and organoleptic characteristics.   The research methods used are ultraviolet and visible spectroscopy (UV-Vis), infrared spectroscopy (FTIR), high performance liquid chromatography (HPLC), thin layer chromatography (TLC), Kjeldahl method, atomic absorption spectroscopy (AAS), sensory analysis, surveys and questionnaires.   The results of the research showed that chickpea-based hummus contains 20-25 % protein, a significant amount of dietary fiber, antioxidants and minerals. Sensory analysis has revealed a high assessment of the organoleptic properties of the product, which indicates its acceptability by consumers.   Conclusions. The results obtained emphasize the value of hummus as a functional product in the diet, helping to maintain health and prevent various diseases. Considering its nutritional properties and pleasant taste, hummus can be an excellent addition to the diet of both vegetarians and people seeking a balanced diet. Further studies could be aimed at assessing the long-term health effects of hummus, its role in diets, and its impact on gut microflora.